Nilai Kearifan Lokal Pada Rumah Adat Dulohupa Kota Gorontalo - Masruroh Masruroh; Sunarty Suly Eraku; Wiwin Kobi; Nadiya Tamau (Universitas Mataram, 2023)
In the midst of the rampant currents of globalization, where humans are busy with modern concepts and thoughts, indigenous peoples are trying to continue to carry out and maintain their traditions, so that culture remains preserved along with the development of globalization. Dulohupa traditional house is one of the Traditional Houses in the Gorontalo area, there are local wisdom values in the Dulohupa traditional house that have meanings and principles in various aspects of the life of the Gorontalo people. The purpose of this study is to introduce local wisdom in the Dulohupa Traditional House in Gorontalo. This study used descriptive qualitative method, the subjects in this study were obtained using interview techniques to information consisting of managers and local communities. The results of this study show that the Dulohupa traditional house consists of elements that have their own characteristics in the form of a stage that describes the house as a human body. The roof part symbolizes the head, the body of the house depicts the body, and the support of the house depicts the legs. The philosophical value of each component of the building includes the value of trust, the value of responsibility, the value of unity and oneness.